2021
DOI: 10.1007/s10010-021-00470-1
|View full text |Cite
|
Sign up to set email alerts
|

CertBench: conclusions from the comparison of certification results derived on system test benches and in the field

Abstract: This paper presents measurement results of the world wide first successful certification the electrical properties of a wind turbine, solely based upon measurements obtained at a system test bench with HiL-System and grid emulator. For all certification relevant tests the results are compared to field measurements. The impact of the real-time models in the HiL-System as well as the converter-based grid emulator are discussed in this paper. For full converter wind turbine, different requirements for the model d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…The experimental results showed that, with the given HiL systems, it is possible to conduct certification measurements at the test bench, which lead to results comparable to results from field measurements. As shown in [28], this is not only true for the few tests discussed in this paper, but also for many others and at other nacelle test benches. However, the analysis in this paper also illustrated in detail that a limited accuracy or errors of the HiL systems, their simulation models, and controls could easily compromise the quality of the certification result.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The experimental results showed that, with the given HiL systems, it is possible to conduct certification measurements at the test bench, which lead to results comparable to results from field measurements. As shown in [28], this is not only true for the few tests discussed in this paper, but also for many others and at other nacelle test benches. However, the analysis in this paper also illustrated in detail that a limited accuracy or errors of the HiL systems, their simulation models, and controls could easily compromise the quality of the certification result.…”
Section: Discussionsupporting
confidence: 60%
“…This project achieved the worldwide first wind turbine certification, solely based upon test bench measurements by means of the German FGW TR3 guideline. An overview of the results [28], and some results on MHiL- [29] and PHiL-specific [30] aspects have been published already.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, grid emulators using a fast voltage control with 1 kHz~3 kHz bandwidth can emulate 0%~130% of nominal voltage within 20 ms [7], [8]. However, the 130%~160% overvoltage and the multi-consecutive faults are not easy to achieve [7], [18]. Further, the impact of reactive current injection by DUT on the emulated voltage profile is overlooked in existing MMC-based grid emulators [4], [5].…”
Section: Synthetic Grid Impedancementioning
confidence: 99%
“…The concept of a certification process using a system test bench was investigated in the research project CertBench [7]. In this project the LVRT behavior of a WT on two different test bench setups are compared to field tests [8].…”
Section: Introductionmentioning
confidence: 99%